PERAN LINGKUNGAN DALAM PEMBENTUKAN PENDIDIKAN ANAK: PERSPEKTIF PEMIKIRAN IBNU KHALDUN - Khoiriyah, Nurul Asma; Jinan, Mutohharun (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Education in the modern era serves not only as a means of transferring knowledge but also as a primary tool in building individual character and advancing society. Ibn Khaldun's thinking emphasizes that education is strongly influenced by the family, school, and community environments, which shape children's mindsets, behaviors, and moral values. A religious and communicative family environment, a school that encourages intellectual development, and a society that upholds the values ??of justice, equality, and cooperation are important factors in creating a holistic education. This article examines Ibn Khaldun's educational thinking, which emphasizes the balance between naqli (the natural) and aqli (the rational) knowledge, as well as the importance of instilling adab (good manners) in the educational process. This research demonstrates that good education must pay attention to the interaction between individuals and their social environment and focus on building strong character. In the context of globalization and technological advancement, the influence of social media and the social environment is a determining factor in children's character development. The conclusion of this study is that children's education must involve synergy between families, schools, and communities to shape a generation that is intellectually intelligent, has noble character, and cares about social life. ABSTRAK Pendidikan di era modern tidak hanya berfungsi sebagai sarana transfer ilmu pengetahuan, tetapi juga sebagai alat utama dalam membangun karakter individu dan kemajuan masyarakat. Pemikiran Ibnu Khaldun menekankan bahwa pendidikan sangat dipengaruhi oleh lingkungan keluarga, sekolah, dan masyarakat, yang membentuk pola pikir, perilaku, serta nilai-nilai moral anak. Lingkungan keluarga yang religius dan komunikatif, sekolah yang mendorong perkembangan intelektual, serta masyarakat yang menjunjung tinggi nilai keadilan, kesetaraan, dan kerja sama, merupakan faktor penting dalam menciptakan pendidikan yang holistik. Artikel ini mengkaji pemikiran pendidikan Ibnu Khaldun, yang menekankan keseimbangan antara ilmu naqli dan aqli, serta pentingnya penanaman adab dalam proses pendidikan. Penelitian ini menunjukkan bahwa pendidikan yang baik harus memperhatikan interaksi antara individu dan lingkungan sosialnya, serta berfokus pada pembentukan karakter yang kuat. Dalam konteks globalisasi dan kemajuan teknologi, pengaruh media sosial dan lingkungan sosial menjadi faktor penentu dalam perkembangan karakter anak. Kesimpulan dari studi ini adalah bahwa pendidikan anak harus melibatkan sinergi antara keluarga, sekolah, dan masyarakat untuk membentuk generasi yang cerdas secara intelektual, berakhlak mulia, dan peduli terhadap kehidupan sosial.